CLASSIFICATION – THE BEGINNING AND THE END OF A RESEARCH (Scientific journal of the Fergana State University, 2023)
The article is devoted to the process of classification assigning the essence of any research and the analysis of basic concepts related to it. Different approaches to classification in linguistics and the steps of linguistic classification are explained.